Sampling protocol to assess Aspergillus section fumigati in woodworking environments - Dias, Marta (2025)
Azole fungicides are commonly used in sawmills to protect wood against the wood-destroying basidiomycete fungi. Azole-resistant Aspergillus section Fumigati has previously been identified in these environments. Here we aimed to establish a sampling protocol to efficiently isolate Aspergillus section Fumigati in woodworking environments. The sampling campaign was conducted between December 2022 and November 2023 in 13 DIY stores and 6 sawmills. Both active and passive sampling methods were used. A total of 370 Aspergillus section Fumigati isolates were recovered from the accessed environments with particularly high efficiency using DG18 incubated at 37 °C. Both active and passive sampling media had a similar number of isolates. Regarding Andersen's six-stage air sampler, stage 5 had the highest number of isolates in both woodworking environments. Data presented in this study validated the used protocol to assess Aspergillus section Fumigati in woodworking environments to enable Occupational Health Services to prioritize interventions in these specific occupational environments to perform accurate exposure assessment and detailed risk assessment and management.